2005
DOI: 10.1071/ea03174
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensory protocol for testing palatability of sheep meats

Abstract: A total of 108 grill and 108 roast samples were prepared from lamb (n = 10) and mutton (n = 8) carcasses for sensory testing using a consumer taste panel. Grill and roast samples were prepared from the left and right sides of the carcass, respectively, using longissimus, biceps femoris, gluteus medius, serratus ventralis and semimembranosus. Due to size constraints, muscle from both sides was used to form grill samples for the vastus lateralis, and roast samples from the triceps brachii. Grill and roast sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 6 publications
1
32
1
Order By: Relevance
“…The taste-panel methods were modified from Thompson et al (2005) and are further detailed in this paper. The cut of meat used was the LL muscle starting from the lumbar-sacral joint down to roughly the 12th rib.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The taste-panel methods were modified from Thompson et al (2005) and are further detailed in this paper. The cut of meat used was the LL muscle starting from the lumbar-sacral joint down to roughly the 12th rib.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The measurement of eating quality in this program has been based on untrained consumer taste panels very much along the lines of the research used to underpin the Meat Standards Australia beef grading scheme (Meat Standards Australia 2002) and is described in the 'Methodology and Statistics' section of this special edition. This methodology is unique and it is important that the readers understand the rigorous nature of the design of the consumer taste panels that can be found in Thompson et al (2005aThompson et al ( , 2005b. Across all the research, about 5600 consumers were used, such that each cut of meat was tested by 10 consumers who scored it for tenderness, juiciness, flavour liking and overall liking (0-100).…”
Section: The Meat and Livestock Australia Lamb And Sheep Meat Eating mentioning
confidence: 99%
“…While the 2 ages were possibly confounded by subtle breed difference, the results are consistent with the other studies presented here. Likewise, Thompson et al (2005b) showed a clear age effect, which was not surprising considering the age difference (9 v. 96 months).…”
Section: Sheep Agementioning
confidence: 96%
“…The matching of muscles by age with recommended cooking method is a critical control point at retail for ensuring consumer satisfaction. To this end, Thompson et al (2005b) present a clear series of tables that can be translated into specific recommendations for matching muscles and age to cooking method. Pleasants (2005) took the eating quality data collected in this program and constructed a linear model of the sensory variables to derive an eating quality rate on a scale of 3: unsatisfactory, good everyday, superior.…”
Section: Meat Ageing Packaging and Display Lifementioning
confidence: 99%
See 1 more Smart Citation